The threatening speech in the Mahabharata epic by Nyoman S. Pendit: A pragmatic perspective - Fitrah, Yundi; Fitriah, Siti; Putri, Aprilia Kartika; Putra, Yoga Mestika; Hasibuan, Selamat Husni (Diksi, 2024)
The main aim of this research is to reveal the form and meaning of threatening speech in the Mahabharata novel by Nyoman S. Pendit. This research is worth carrying out considering that there is no research which discusses about the threat speech in ancient Javanese classical epics through a pragmatic perspective. The methodology approach is a mixed methods which refers to combine a qualitative and quantitative research techniques. The data of threatening speech is analysed using Miles and Huberman techniques (1984). The theory used to determine the indicators of threatening speech is based on Fraser's (1998) theory, to analyze the form using Searle's (1979) theory, and to explain the meaning using Lí¶bner's (2013) theory. The results of the data analysis showed that the forms of threatening speech that tended to be used is expressive illocutions. This  illocution aims to express the psychological attitude or feelings of the speaker towards his/her interlocutor. So, the power of speech that reaches the interlocutor is a form of feelings of inferiority and humiliation due to the use of diction that tends to be negative such as the statements of "˜perempuan jahannam', "˜manusia jahannam', "˜lelaki penuh dosa','manusia celaka', "˜najis',  and "˜pengecut'. Finally, the meaning of threatening speech that tends to be found is the meaning of speech. This indicates that the meaning of a threatening speech cannot be understood easily. So,  it is necessary to consider the context of the utterance to understand it.